How to care for the brought in dead and their relatives. A qualitative study protocol based on interpretive description. (7th April 2020) - Bove, Dorthe Gaby; Rosted, Elizabeth; Prip, Anne; Jellington, Maria Omel; Timm, Helle; Herling, Suzanne Forsyth
Abstract: Aim: This project has two aims: (a) What do relatives to brought in dead (BID) describe as helpful and supportive care when they arrive at the emergency department to see and say goodbye to a deceased? (b) What do nurses describe as good nursing practice for BID persons and their relatives and what may hinder or facilitate this practice in an emergency setting? Design: A qualitative study in the methodology interpretive description. Methods: Data will be collected through three data sources: Individual interviews with relatives to BID persons, participant observations of relatives to BID persons during their presence in the emergency department and focus group interviews with emergency nurses. Discussion: Brought in dead persons and their relatives are received and cared for in emergency departments by emergency nurses. Knowledge of how to render care for the relatives to BID persons in an acute setting including what skills and competences this require of the nurses is warranted. We need to explore, describe, and comprehend the experiences of both the relatives and the nurses to point out potential areas of improvement. Impact: This study is a protocol of an Interpretive Description study offering insight into considerations and reflections in designing the study. Abstract : 目的: 该项目有两个目的:(a)当亲属到达急诊室与送来的死者告别时, 如何描述对于死者的护理起到帮助性和支持性的作用?(b)护士如何描述送来的死者及其亲属的良好护理实践, 以及在紧急情况下这一做法的可能助力和阻力因素? 设计: 对方法论解释性描述的定性研究 方法: 通过三种数据来源收集数据:对送来的死者亲属的个人访谈、送来的死者亲属在急诊间的参观察和对急诊护士的焦点小组访谈。 讨论: 急诊间由急诊护士接送送来的死者及其亲属。了解如何在紧急情况下向亲属提出为送来的死者进行护理的方法, 包括护士需要具备的技能和能力。我们需要探索、描述和理解亲属和护士双方在这一方面的经历, 指出潜在的改进领域。 影响: 本研究采取解释性描述研究方案, 提供设计研究时的考虑和思考。: